Incidence of Acute Chagas Disease in the state of Pará-Brazil, between 2010 and 2020 (Research, Society and Development, 2022)
Inserted in the group of neglected diseases, Chagas disease is an infection caused by the protozoan Trypanosoma cruzi, being responsible, in 2021, for 7 million infections. Despite being a vector disease, its main form of transmission is through the oral route, mainly in Brazil, north and northeast regions. In recent decades there has been a transition in the epidemiological profile of CD, with an increasing prevalence in urban areas. Therefore, the objective of this study is to investigate the incidence of acute Chagas disease (ACD) in the state of Pará. Thus, an exploratory, quantitative and descriptive study was carried out, based on the databases of the Notifiable Diseases Information System - Sinan Net® of the Ministry of Health/SVS, from 2010 to 2020. The region Norte had a maximum peak in the years 2016 and 2018, with 355 cases in each, with Pará being the state with the highest incidence and Abaetetuba the city with the most cases in the analyzed time (258). Therefore, the data showed that DCA depends on numerous factors, such as: political-economic issues, sociocultural aspects, migratory currents and ecological imbalance. Thus, the process of health education for the population, combined with the training of traders, is essential to reduce the incidence of ACD.